Robustness of Bayesian Methods in Healthcare System Assessment: A Comprehensive Review - Akhtar, Md. Tanwir (International Journal of Statistics in Medical Research, 2025)
Background: Healthcare systems generate heterogeneous, incomplete, and evolving data; methods that combine prior knowledge with new evidence are needed. Aim: The present research critically evaluates the usefulness and resilience of Bayesian methods for healthcare system assessment. Scope: This study synthesizes foundational principles and contrasts with frequentist approaches; examines applications across quality of care benchmarking, health economic evaluation, epidemiologic surveillance, resource allocation, policy appraisal, and personalized medicine; and highlights computational advances enabling practical deployment. Key Findings: Bayesian techniques provide partial pooling through hierarchical models, formal incorporation of prior information, accurate probabilistic inference, and dynamic updating as data accumulates. These features give more stable estimates in sparse settings, transparent quantification of uncertainty, and decision‑relevant outputs (e.g., posterior probabilities and cost-effectiveness acceptability). Modern samplers and approximate inference make complex models tractable, yet results remain sensitive to prior specification and data quality, stressing the need for validation, sensitivity analysis, and clear reporting. Conclusion: Bayesian methods offer a meticulous, flexible framework for assessing performance, value, and equity in healthcare systems. They can enhance policy-making and clinical decision support when paired with principled prior elicitation, robust computation, and reproducible workflows. Next, the practical recommendations and research priorities to accelerate responsible adoption across healthcare analytics were outlined. At the end, this review highlights both methodological robustness and translational potential, positioning Bayesian methods as indispensable for evidence-based healthcare decision-making.